Evaluating contemporary pain management practices in thyroid and parathyroid surgery: A national survey of head and neck endocrine surgeons. Issue 7 (13th February 2019) - Ferrell, Jay K.; Singer, Michael C.; Farwell, D. Gregory; Stack, Brendan C.; Shindo, Maisie
Abstract: Background: There is currently a lack of evidence‐based guidelines regarding postoperative opioids after thyroid and parathyroid surgery. This study aimed to objectively characterize contemporary postoperative pain management practices via a national survey of head and neck endocrine surgeons. Methods: A standardized electronic survey was distributed to the membership of the American Head and Neck Society's Endocrine section. Results: A total of 102 surgeons completed the survey representing a 34% response rate. In all, 65.7% of respondents utilize opioids with wide variations in the total morphine equivalents prescribed. Practice environment (χ 2 = 10.0; P  = 0.04) and performing preoperative pain counseling (χ 2 = 9.7; P = 0.002) were significantly associated with a decreased likelihood of prescribing postoperative opioids. Utilization of non‐opioid pain management strategies was common and significantly associated with performing outpatient surgery (χ 2 = 6.2; P  = 0.013) and preoperative pain counseling (χ 2  = 4.5; P  = 0.034). Conclusions: Pain management practice patterns vary significantly among head and neck endocrine surgeons which further emphasize the need for evidence‐based guidelines.